Impact of once-daily extended-release quetiapine fumarate on hospitalization length in patients with acute bipolar mania. (January 2015) - Bonafede, Machaon; Locklear, Julie C; Wahlqvist, Peter; Fajutrao, Liberty; Szamosi, Johan; Pan, Katy; Eriksson, Hans
Aims: Evaluate the impact of quetiapine extended release (XR) versus quetiapine immediate release (IR) on hospitalization length in acute bipolar mania using Truven Health Analytics MarketScan ® Hospital Drug Database.Patients & methods: Generalized linear model analyses were used, adjusting for patient and hospital characteristics.Results: Using data from 3088 discharges, quetiapine XR reduced hospitalization length by 6.7% versus quetiapine IR (p = 0.11; no statistically significant differences between groups), corresponding to 0.6 fewer days in hospital. Excluding the outlier, quetiapine XR significantly reduced hospitalization length by 9.6% versus quetiapine IR (p = 0.02), corresponding to 0.9 days.Conclusion: Inpatient use of quetiapine XR in acute bipolar mania may be associated with reduced hospitalization length (7–10%), possibly owing to the faster titration schedule versus quetiapine IR.